Development of Analytical Method for Determination of Palm-Based Hydrotreated Vegetable Oil (Hvo) in Diesel Blends Using Gas Chromatography: Preliminary Study - Sylvia Ayu Bethari; Handajaya Rusli; Muhammad Bachri Amran (Scientific Contributions Oil and Gas, 2025)
Hydrotreated vegetable oil (HVO) is a renewable paraffinic biofuel derived from the catalytic hydrotreatment of triglycerides, particularly from palm oil. Because HVO's hydrocarbon structure is so similar to petroleum diesel, it can be mixed directly with regular diesel fuel. But because of this structural similarity, it is very difficult to accurately quantify HVO in diesel blends, which is essential for maintaining fuel quality and complying with regulations. In this study, gas chromatography–mass spectrometry (GC-MS) was used to identify the compounds and gas chromatography–flame ionization detection (GC-FID) was developed to quantify biofuel HVO. The chromatographic profiles of diesel, HVO, and biodiesel displayed distinct hydrocarbon distributions. Two diagnostic peaks at retention times of 17.5 – 17.7 minutes, identified as heptadecane and 2,6,10,14-tetramethylpentadecane (pristane), were used for preliminary identification. The heptadecane peak, present in both diesel and HVO, was selected as a quantifier, while the heptadecane-to-pristane ratio of 1.25 in diesel was applied as a correction factor. The accuracy of the method was confirmed by the observation of a strong linear correlation (R2 = 0.9991) for HVO concentrations ranging from 0 to 40% v/v. Recovery rates ranging from 97.0% to 102.2% further illustrated how reliable the method is for routinely analyzing the amount of HVO in diesel blends.